Complete Remission after Sequential Therapy of Drug Eluting Beads Transarterial Chemoembolization and Liver Resection in Large Solitary Nodule Hepatocellular Carcinoma - Juferdy Kurniawan; Andri Sanityoso Sulaiman; Sahat Basana Romanti Ezer Matondang; Toar Jean Maurice Lalisang; Ening Krisnuhoni; Steven Zulkifly (Case Reports in Hepatology)
Hepatocellular carcinoma (HCC) is the fifth most prevalent and the second highest cause of death among cancer. The treatment of large solitary nodule HCC is still challenging. Transarterial chemoembolization (TACE) and liver resection are two modalities of therapy in HCC management. However, recurrence rate from each therapy is relatively high. We report a case of 46-year-old man diagnosed with large solitary nodule HCC, who was treated with drug eluting bead TACE (DEB-TACE) prior to liver resection. Studies about this combination are still limited and showed various results.